Identification of Five NK Cell-Related Hub Genes in COPD Using Single-Cell RNA Sequencing Analysis - Deng X; Yang X; Gan Z; Huang H; Yang J (Journal of Inflammation Research, 2025)
Xiaojie Deng,1,* Xiahui Yang,1,* Zhihua Gan,2 Huaxing Huang,1 Jun Yang1 1Department of Pulmonary and Critical Care Medicine, The Second Affiliated Hospital of Guangzhou Medical University Guangzhou, Guangdong, People’s Republic of China; 2Department of Pulmonary and Critical Care Medicine, The Affiliated Brain Hospital, Guangzhou Medical University Guangzhou, Guangdong, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jun Yang, Email yangjun2001@gzhmu.edu.cnBackground: COPD is a healthcare problem. However, the underlying mechanism remains unclear. Our study aimed to explore the key genes involved in immune infiltration in COPD using bioinformatic tools.Methods: In this study, scRNA-seq analysis was utilized to explore specific marker genes of each immune cell subtype in COPD. TSNE analysis was used to evaluate the relationship between each immune cell cluster. Lasso regression identified 21 genes as characteristics of COPD modulated by the single-cell NK cell subpopulation. The “limma” package was used for differentially expressed analysis. The pseudotime analysis reveals the continuous changes of NK cells along their developmental trajectory. Further, we constructed a hub gene network to examine the correlation between hub genes and immune factors, transcriptional regulation factors, and potential therapeutic drugs. GO and KEGG enrichment analysis revealed the biological functions of the hub genes. RT-qPCR was used for validation of the five hub in COPD patients.Results: NK cell subtypes are closely related to other immune cell subtypes and considered as the most important immune cells in the immune microenvironment of COPD patients. LASSO regression identified 21 genes as NK cells-characteristic genes for COPD. The GSE57148 as the training set has a AUC of 0.9489 and GSE8581 as the validation set has a AUC of 0.7303. The GO semantic similarity further confirmed five NK cell-related hub genes, C1orf56, S100A6, IGFBP7, ANXA1, and PTPN7. RT-qPCR experiment revealed that the mRNA expression of five hub genes in the normal group was lower than that in the disease group. We also found that five hub genes correlated with immune cell infiltration. The potential therapeutic agents for COPD may be zalcitabine, PP-2, PD-98059, and TGX-221 based on the CMap database prediction.Conclusion: We proposed that peripheral NK cells may play a role in the pathogenesis of COPD through bioinformatic analysis. These hub genes may provide insights into mechanistic research and new targets for new therapies in patients with COPD.Keywords: COPD, hub genes, single-cell RNA-sequencing, NK cell, immune infiltration